2021
DOI: 10.3390/genes12020305
|View full text |Cite
|
Sign up to set email alerts
|

Sex Determination and Differentiation in Decapod and Cladoceran Crustaceans: An Overview of Endocrine Regulation

Abstract: Mechanisms underlying sex determination and differentiation in animals are known to encompass a diverse array of molecular clues. Recent innovations in high-throughput sequencing and mass spectrometry technologies have been widely applied in non-model organisms without reference genomes. Crustaceans are no exception. They are particularly diverse among the Arthropoda and contain a wide variety of commercially important fishery species such as shrimps, lobsters and crabs (Order Decapoda), and keystone species o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 170 publications
0
15
0
Order By: Relevance
“…In contrast, environmental cues stimulate male production [1,2]. Previous studies revealed that environmental cues are converted into sesquiterpenoid signaling and activate the Dsx1 gene [3,4]. This gene codes for the DM-domain transcription factor and orchestrates the male-developmental program [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, environmental cues stimulate male production [1,2]. Previous studies revealed that environmental cues are converted into sesquiterpenoid signaling and activate the Dsx1 gene [3,4]. This gene codes for the DM-domain transcription factor and orchestrates the male-developmental program [5].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, under a stressed environment such as shortened photoperiod, a lack of food, and/or increased population density, D. magna produces male offspring that are genetically identical to females [1,2]. The environmental cues for male determination stimulate the neuroendocrine system and secrete sesquiterpenoid, which promotes the production of parthenogenetic eggs that are destined to develop into males [3,4]. The male developmental program is implemented by the male-specific expression of the DM-domain containing transcription factor named Doublesex1 (Dsx1) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies on sex determination/differentiation on crustaceans have been conducted, compared to active studies on Decapoda (e.g., crabs, lobsters, and shrimps), research on Branchiopoda is still limited to Daphnia . Species that are easy to grow and have availability of genome sequences and embryonic developmental data are useful as new model organisms for crustaceans [ 74 ]. As mentioned in the introduction, Artemia has several advantages as a model organism for studying sex determination systems.…”
Section: Discussionmentioning
confidence: 99%
“…Sex determination (SD) is highly complex in vertebrates and can be classified into environmental sex determination (ESD), genetic sex determination (GSD), and their combination ( Bachtrog et al, 2014 ; Li & Gui, 2018 ; Nagahama et al, 2021 ; Rajendiran et al, 2021 ; Renn & Hurd, 2021 ). The GSD system can be further classified into the male heterogametic system (sex chromosome: XX/XY), female heterogametic system (sex chromosome: ZW/ZZ), and polygenic SD system ( Geffroy et al, 2021 ; Nagahama et al, 2021 ; Toyota et al, 2021 ). The two sex chromosome systems have been identified in fish, but most species have no obvious morphological sex chromosome ( Feller et al, 2021 ; Nakamura, 2009 ; Sarre et al, 2011 ; Xue et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%